Use distributive property:
3x-5y+8x+14y
3x+8x-5y+14y
11x+9y
2006-12-18 13:35:47
·
answer #1
·
answered by Anonymous
·
4⤊
1⤋
First: get rid of parenthesis > distribute -(-8x) into 8x because two negatives become a positive:
= 3x - 5y + 8x + 14y
Second: combine like terms > x-variables together and y-variables together:
= 3x + 8x - 5y + 14y
= 11x + 9y
2006-12-18 13:56:18
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
2⤊
0⤋
= 3x - 5y + 8x + 14y
= 3x + 8x - 5y + 14y
= (3+8)x + (-5+14)y
= 11x + 9y.
2006-12-18 12:59:23
·
answer #3
·
answered by Scarlet Manuka 7
·
3⤊
0⤋
3x+8x+14y-5y
=11x+9y
Like terms are those with the same letter coeffecient.
2006-12-18 13:00:00
·
answer #4
·
answered by Anonymous
·
3⤊
0⤋
3x-5y+8x+14y
3x+8x-5y+14y
=11x+9y
2006-12-18 12:59:48
·
answer #5
·
answered by raj 7
·
4⤊
0⤋
3x - 5y - (-8x) + 14y
= 11x + 9y
QED
2006-12-18 13:03:59
·
answer #6
·
answered by CSUFGrad2006 5
·
3⤊
0⤋
3x - 5y - (-8x) +14y
3x+8x-5y+14y
11x+9y
2006-12-18 12:59:07
·
answer #7
·
answered by yupchagee 7
·
3⤊
0⤋
11x+9y
2006-12-18 13:00:50
·
answer #8
·
answered by Anonymous
·
3⤊
0⤋
That's not a question. Or even a sentence.
2006-12-18 12:58:53
·
answer #9
·
answered by Anonymous
·
0⤊
3⤋